2020
DOI: 10.18060/22576
|View full text |Cite
|
Sign up to set email alerts
|

Political Primacy and MSW Students' Interest in Running for Office

Abstract: Although social workers are understood to participate in politics more than the general public, little is known about their interest in running for office. To understand how individuals in "helping" professions like social work may think about running for office, this study introduces the concept of political primacy. Political primacy refers to the value individuals assign to elected office's ability to make a difference, relative to alternative ways of making a difference. Using data from the Michigan Law & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Later studies found that SW managers engage more in policy because they have more opportunities, greater expectations and more knowledge and self-efficacy (Makaros et al, 2020). Finally, studies have identified personality traits (Schwartz-Tayri, 2020), gender (Meehan, 2019;Ostrander et al, 2019;Shin, 2020) and ethnicity (Bent-Goodley, 2003;Lane and Humphreys, 2011;Nouman and Azaiza, 2021;Darawshy et al, 2022) as factors that influence SWs' engagement in policy routes.…”
Section: Explanationsmentioning
confidence: 99%
“…Later studies found that SW managers engage more in policy because they have more opportunities, greater expectations and more knowledge and self-efficacy (Makaros et al, 2020). Finally, studies have identified personality traits (Schwartz-Tayri, 2020), gender (Meehan, 2019;Ostrander et al, 2019;Shin, 2020) and ethnicity (Bent-Goodley, 2003;Lane and Humphreys, 2011;Nouman and Azaiza, 2021;Darawshy et al, 2022) as factors that influence SWs' engagement in policy routes.…”
Section: Explanationsmentioning
confidence: 99%